2014
DOI: 10.1016/j.jmapro.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Dimpling process in cold roll metal forming by finite element modelling and experimental validation

Abstract: (2014) Dimpling process in cold roll metal forming by finite element modelling and experimental validation. Journal of Manufacturing Processes, 16 (3). pp. 363-372. ISSN 1526-6125 This version is available from Sussex Research Online: http://sro.sussex.ac.uk/48964/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In reality, the thickness of dimpled plate slightly varies at different locations around the dimple valley [24]. However, it was assumed that the thickness was uniform across the entire plate.…”
Section: Numerical Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…In reality, the thickness of dimpled plate slightly varies at different locations around the dimple valley [24]. However, it was assumed that the thickness was uniform across the entire plate.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…The process uses a pair of rollers with rows of specially shaped teeth that form the dimple shapes from both sides of the plain sheet, as shown in Figure 1 [24]. The dimpled sheet can then be progressively formed into a desired profile by passing through a series of rolls, arranged in tandem, or by press braking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dimpled sheets are then formed into desired profiles by passing through a series of rolls or press braking. Several previous numerical and experimental research has revealed that the strengths of dimpled steel sheets are significantly greater than those of the original plain steel sheets [21][22][23][24][25][26][27]. The increase in strength is mainly due to work hardening developed throughout the forming process.…”
Section: Introductionmentioning
confidence: 99%